In Vitro Sensitivity to Venetoclax and Microenvironment Protection in Hairy Cell Leukemia - Vereertbrugghen, Alexia; Colado, Ana; Gargiulo, Ernesto; Bezares, Raimundo Fernando; Fernández Grecco, Horacio; Cordini, Gregorio; Custidiano, Maria del Rosario; François, Jean-Hugues; Berchem, Guy; Borge, Mercedes; Paggetti, Jerome; Moussay, Etienne; et al. (Frontiers in Oncology, 2021)
Current standard treatment of patients with hairy cell leukemia (HCL), a chronic B-cell neoplasia of low incidence that affects the elderly, is based on the administration of purine analogues such as cladribine. This chemotherapy approach shows satisfactory responses, but the disease relapses, often repeatedly. Venetoclax (ABT-199) is a Bcl-2 inhibitor currently approved for the treatment of chronic lymphocytic leukemia (CLL) and acute myeloid leukemia (AML) adult patients ineligible for intensive chemotherapy. Given that HCL cells express Bcl-2, our aim was to evaluate venetoclax as a potential therapy for HCL. We found that clinically relevant concentrations of venetoclax (0.1 and 1 µM) induced primary HCL cells apoptosis in vitro as measured by flow cytometry using Annexin V staining. As microenvironment induces resistance to venetoclax in CLL, we also evaluated its effect in HCL by testing the following stimuli: activated T lymphocytes, stromal cells, TLR-9 agonist CpG and TLR-2 agonist PAM3. We found decreased levels of venetoclax-induced cytotoxicity in HCL cells exposed for 48 h to any of these stimuli, suggesting that leukemic B cells from HCL patients are sensitive to venetoclax, but this sensitivity can be overcome by signals from the microenvironment. We propose that the combination of venetoclax with drugs that target the microenvironment might improve its efficacy in HCL.